Temperature induced amyloid production, biofilm formation and fitness in marine Bacillus sp. (July 2021) - Rajitha, K.; Nancharaiah, Y.V.; Venugopalan, V.P.
Abstract: Biofilm development in industrial cooling systems is influenced by the prevailing environmental conditions. However, the impact of temperature rise, common to industrial cooling systems, on biofilms is unclear. Here, the effect of temperature increase on biofilm formation and the extracellular polymeric substances (EPSs) production in marine biofilm forming Bacillus species thriving in the cooling water system of an operating power plant was investigated. Experimental data showed that biofilm formation in Bacillus sp. was significantly increased by up to 90% at 37–45 °C as compared to ambient seawater temperature of 30 °C. Enhanced biofilm growth at 37 °C and above was found to be associated with increased production of EPSs. Biofilm growth and EPSs production were increased by 47% and 62%, respectively, at 45 °C as compared to at 30 °C. Detailed analysis indicated that production of amyloid, important structural EPSs in the Bacillus biofilms, was positively correlated with an increase in incubation temperature. Amyloid production in turn altered the characteristics of Bacillus colony biofilms including morphology, roughness and wetting behaviour, thus facilitating fitness at higher temperatures. Biofilm formation and amyloid production are likely important physiological determinants for survival strategies of Bacillus persistence in the warm environmental settings of seawater cooling system. Graphical abstract: Image 1 Highlights: B. haynesii modulated the growth pattern to survive at higher water temperatures. Colony roughness, hydrophobicity, and pattern were altered at 37–45 °C. Biofilm formation was induced at higher water temperatures of 37–45 °C. Production of amyloid-like fibers was induced at higher water temperatures. Amyloid and biofilm formation is a survival strategy for Bacillus in warmer settings.